Impact of Online Stress Management Training Program on the Sexual Function of Perimenopausal Women: A Clinical Trial - Leila Neisani Samani; Shima Arjmand; Naeimeh Seyedfatemi; Shima Haghani (نشریه پرستاری ایران)
Background & Aims Sexual dysfunction is one of the problems of transition to menopause in women, which often begins at the age of 45. Virtual education is useful due to its availability, quick response, and attractive presentation methods. This study aims to evaluate the impact of online stress management training on the sexual function of perimenopausal women. Materials & Methods This is a clinical trial with a pre-test/post-test design that was conducted on 50 perimenopausal women aged 40-50 referring to Sohrab Ali Bakhshi comprehensive health center in Shahriar town, Tehran, Iran, in 2022, who were selected using a continuous sampling method. They were divided into five groups of 10 and received stress management training online using WhatsApp at 8 sessions of 30 minutes, two times per week, for four weeks. They completed a sociodemographic/obstetric form and the female sexual function index (FSFI) before, immediately after, 4 weeks after, and 8 weeks after the intervention through self-reporting. The data were analyzed using the paired t-test and ANOVA. Results The FSFI score and the scores of its various domains changed significantly over time (P<0.001). Sexual desire decreased from 3.8 before the intervention to 2.3 at 8 weeks after the intervention (P<0.05). The scores of other domains, including sexual arousal, satisfaction, orgasm, pain, and lubrication, improved significantly (P<0.001). The mean total FSFI score increased from 22.91 before the intervention to 25.22 at 8 weeks after the intervention (P<0.001). No statistically significant differences were found between 4 and 8 weeks after intervention except for the orgasm domain (P=0.016) and the total score (P=0.015). Conclusion The online stress management training program can improve the sexual function of perimenopausal women in the areas of sexual arousal, sexual desire, satisfaction, orgasm, pain, and lubrication.